AN ANALYSIS ON THE ITEMS DIFFICULTY LEVEL OF ENGLISH SEMESTER TEST AT THE TENTH GRADE STUDENTS OF SMAN 3 JAMBI CITY ACADEMIC YEAR 2016/2017 - Adelia Damayanti; Wennyta Wennyta; Khidayatul Munawwaroh (Universitas Batanghari Jambi, 2018)
The purpose of this study is to measure the difficulty level of the English semester test items for the tenth grade students at SMA N 3 Jambi City in the academic year 2016/2017. The sample is 40 students of tenth grade science two and taken by random sampling with lottery. This study is conducted to analyze the test items whether it is conclude in easy, moderate, or difficult items. This study is categorized in mix method research, those are quantitative and qualitative. The instrument used in this study is documentation. The researcher take 40 students’ answer sheets as the data that will be counted how many respondents can answer of each item and has been counted by using formula. The research find that there are 35 items in easy level, 2 items in moderate level, and 3 items in difficult items. And all the items can be said in easy level with the result 0,85 index of difficulty. The researcher also find that there are 12 valid items, and 28 invalid items.Keywords: English Semester Test, Item Analysis, Difficulty Level.